Insecurity, Precarious Work and Labour Markets Challenging the Orthodoxy - Choonara, Joseph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Precarity is a key theme in political discourse, in media and academic discussions of employment, and within the labour movement. Often, the prevailing idea is of an endless march of precarity, rendering work ever more contingent and workers ever more disposable. However, this detailed study of the UK labour force challenges the picture of rising precarity and widespread use of temporary employment, suggesting instead that employment tenure and the extent of temporary work have proved stubbornly stable over the past four decades. Choonara offers a new approach to labour markets, drawing on the theoretical underpinnings of Marxist political economy to interrogate research data from the UK. This book examines why, despite the deteriorating conditions in work, employment relations have remained stable, and offers insight into the extent of subjective insecurity among workers. Insecurity, Precarious Work and Labour Markets will be of use to students and scholars across the sociology of work, labour economics, industrial relations and political economy.
1. Introduction: The Precarity Debate -- 2. Theorists of Transformation -- 3. Conceptualising Precarity and Insecurity -- 4. Is Work Being De-standardised? -- 5. Is Employment Tenure Declining? -- 6. Rethinking Labour Markets -- 7. An Epidemic of Insecurity? -- 8. Conclusions.
Keywords: Industrial sociology; Labor economics; International economic relations; Sociology of Work; Labor Economics; International Political Economy'.